Effect of glycated hemoglobin A1c on the survival of patients with oral squamous cell carcinoma: A multi-institutional database cohort study - Chao, Chun-Yuan; Luo, Sheng-Dean; Chen, Wei-Chih; Wu, Shao-Chun; Chiu, Tai-Jan; Wang, Yu-Ming; Yang, Yao-Hsu; Fang, Fu-Min; Li, Shau-Hsuan; Li, Chung-Yi; Wu, Ching-Nung (Frontiers in Oncology, 2022)
Objectives: Few studies have evaluated the impact of blood glucose levels on cancer prognosis. We investigated the association between hemoglobin A1c (HbA1c) and survival in oral squamous cell carcinoma (OSCC) patients. Materials and Methods: A 19-year retrospective cohort study of OSCC patients was performed using the Chang Gung Research Database to identify and enroll 7279 patients diagnosed with OSCC between January 2001 and June 2020. A total of 3600 patients were recruited after performing 1:2 frequency-matching between patients with DM and non-DM. A Cox’s regression model was used to evaluate the relative hazards of all-cause mortality (ACM) and disease-specific mortality (DSM) in relation to HbA1c. Results: An unadjusted Cox’s regression model indicated that DM, in addition to high levels of HbA1c, were statistically prognostic of poor survival. An adjusted hazard ratio (aHR) of HbA1c ≥ 8% interval at the initial diagnosis of OSCC was statistically higher for DSM (1.25 to 2.24) compared to the non-DM group in different regression models. Considering the effect of sustained HbA1c control in 699 patients, the mean aHR of HbA1c ≥ 9% interval was statistically higher for ACM (1.78 to 2.13) compared to the reference group (7% ≤ mean aHR of HbA1c < 8%). In addition, increased hazards of ACM (2.09 to 2.18) and DSM (2.20 to 2.41) were consistently observed in the highest quartiles of average real variability of HbA1c. Conclusion: Poor and unstable control of HbA1c could strongly predict the risks of mortality in OSCC patients with DM.